2007
DOI: 10.1159/000106775
|View full text |Cite
|
Sign up to set email alerts
|

Laser Capture Microdissection-Microarray Analysis of Focal Segmental Glomerulosclerosis Glomeruli

Abstract: Focal segmental glomerulosclerosis (FSGS) is a major cause of end-stage renal disease. In this report we used laser capture microdissection to purify diseased glomeruli, and microarrays to provide universal gene expression profiles. The results provide a deeper understanding of the molecular mechanisms of the disease process and suggest novel therapeutic strategies. Consistent with earlier studies, molecular markers of the differentiated podocyte, including WT1, nephrin, and VEGF, were dramatically downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 76 publications
(40 reference statements)
4
64
0
Order By: Relevance
“…We used microarrays to reveal the perturbations in gene expression in isolated glomeruli at various time points after podocin inactivation and found a molecular signature unique from other, previously published models of FSGS, [43][44][45] thus, confirming the heterogeneity of FSGS depending on the mechanism by which podocyte injury is incurred. Intriguingly, we found that genes involved in cell-cycle regulation were the earliest genes to be transcriptionally activated in our model.…”
Section: Basic Research Wwwjasnorgsupporting
confidence: 59%
“…We used microarrays to reveal the perturbations in gene expression in isolated glomeruli at various time points after podocin inactivation and found a molecular signature unique from other, previously published models of FSGS, [43][44][45] thus, confirming the heterogeneity of FSGS depending on the mechanism by which podocyte injury is incurred. Intriguingly, we found that genes involved in cell-cycle regulation were the earliest genes to be transcriptionally activated in our model.…”
Section: Basic Research Wwwjasnorgsupporting
confidence: 59%
“…(19) Cxcl1 encodes chemokine (C-X-C motif) ligand 1 (CXCL1), known as growth-related oncogene 1 (GRO1), which could enhance the adhesion of monocytes to matrix protein, (20) and is involved in the atherogenic recruitment of monocytes. (21) At present, there is no evidence of a relationship between CXCL1 and kidney stone formation; on the other hand, simultaneous increased expression of CXCL1 and OPN in the transplanted kidney, (22) focal segmental glomerulosclerosis glomeruli, (23) and colon cancer (24) suggest that CXCL1 could play an important role with osteopontin in kidney stone formation or elimination. Increased expression of H2-Eb1 (encodes MHC class II) and Tgfb1 (encodes TGF-b1) could be associated with helper T-cell activation via antigen presentation.…”
Section: Discussionmentioning
confidence: 93%
“…In the heart, Sox9 is required for proper organization the valvular ECM proteins (60), whereas in the gonads, Sox9 regulates many ECM proteins as well as modifiers of the ECM such as matrix metalloproteinases (61,62). Sox9 also plays a role in fibrotic and sclerotic disorders in various tissues, in which Sox9 causes excessive and inappropriate ECM deposition by activating ECM proteins (63)(64)(65)(66)(67)(68). Furthermore, Sox9 plays a critical role during chondrogenesis (30), and ChiP analysis in chondrocytes has shown that Sox9 directly binds to loci of 18 different ECM genes, including Col2a1 (69).…”
Section: Discussionmentioning
confidence: 99%